Development and Management of Water in Wetland - Soedodo Hardjoamidjojo; Budi I. Setiawan (Jurnal Keteknikan Pertanian, 2001)
This paper describes potentials as well as obstacles in developing wetland for agricultures. Historical backgrounds of wetland utilization for agricultures Indonesia and wetland definition by Ramsar Convention are highlighted. Special emphasis is given to explain physical and hydrological conditions of wetland and opportirnities to develop sustainable agricultural activities based on wetland categories. Current problems in developing wetland, sucsh as land degradation and lost of wetland are enlightened, and a little note is aroused to elucidate the failure of One Million Hectares Project in Central Kalimantan. Finally, prospectivetechnologies for controlling water table were proposed.